HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PADA PASIEN TB DI WILAYAH KERJA PUSKESMAS BENGKURING SAMARINDA - windah febriyani; Ratanto Ratanto; Arifin Hidayat (MNJ (Mahakam Nursing Journal), 2022)
The high increase in DM cases each year as well as complications caused by DM disease is quite worrying the consequences of a shift in lifestyle changes which is a public health problem The high increase in DM cases each year as well as complications caused by DM disease is quite worrying where the consequences of a shift in lifestyle changes which is a public health problem. Purpose this study aims to determine the relationship of lifestyle with Diabetes Mellitus disease in Prolanis patients in Elderly Posyandu working area of ​​Public health Palaran. This research is analytic with cross sectional research design. The population of 226 proline patients with the number of samples of 48 respondents with random sampling technique. Data were collected using questionnaires. Place of study at Posyandu Lansia working area of ​​Puskesmas Palaran. Data were analyzed by chi-square test. The lifestyle factors most closely related to the incidence of DM are physical activity habits with a pvalue of 0.048. There is a lifestyle relationship with DM disease in DM patient with pvalue = 0,018 with OR = 0,15. The most DM risky lifestyle factor is physical activity.